1991
DOI: 10.1071/pp9910543
|View full text |Cite
|
Sign up to set email alerts
|

Factors Determining Host Recognition in the Clover-Rhizobium Symbiosis

Abstract: Rhizobia are microbes that exploit host plants as a nutritional source but cause little or no host damage. They may provide, through biological nitrogen fixation, a valuable source of nitrogen for plant growth. Different rhizobia nodulate a limited range of plants. In this review we will show that host range specificity is determined by the success or otherwise of communication events between the interacting partners. To infect different plant species, a distinct cocktail of phenolic compounds (flavonoids) is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
1

Year Published

1992
1992
2008
2008

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 42 publications
0
21
0
1
Order By: Relevance
“…Compounds with these structures are themselves potential nod gene inducers and could be involved in interactions with the nodD gene product. Chalcones especially have been reported to serve as more potent nod gene inducers than other flavonoid molecules (9), and this feature has largely been attributed to their open C-ring system (7), which offers increased spatial flexibility during interactions with NodD proteins (5). Chalcones emerging from an initial C-ring fission in the inducer flavonoid may provide additional conformational flexibility during binding to NodD proteins, thereby increasing transcriptional activation of other nod genes.…”
Section: Discussionmentioning
confidence: 99%
“…Compounds with these structures are themselves potential nod gene inducers and could be involved in interactions with the nodD gene product. Chalcones especially have been reported to serve as more potent nod gene inducers than other flavonoid molecules (9), and this feature has largely been attributed to their open C-ring system (7), which offers increased spatial flexibility during interactions with NodD proteins (5). Chalcones emerging from an initial C-ring fission in the inducer flavonoid may provide additional conformational flexibility during binding to NodD proteins, thereby increasing transcriptional activation of other nod genes.…”
Section: Discussionmentioning
confidence: 99%
“…Purified BF-7 was dried, resuspended in nitrogen-free (NF) plant growth medium (13) (12,54). Interestingly, several orcinol-positive components in different fractions from the silica column chromatography were shown by TLC to fulfill the criteria specified above.…”
Section: Methodsmentioning
confidence: 99%
“…symbiosis, the bacterial symbiont expresses several nodulation (nod) genes located on its symbiotic plasmid (pSym) (12,27). The action of certain pSym nod genes is correlated with the production of specific molecules capable of acting as signals to elicit various symbiosis-related morphological responses in the plant root, including root hair deformations (Had), induction of foci of cortical cell divisions (Ccd), and a thick, short root (Tsr) (reviewed in references 2, 3, and 16).…”
mentioning
confidence: 99%
“…Previous research on this topic suggests that molecules from the host plant are required for the expression of symbiotic fungal genes (Koske, 1982;Elias and Safir, 1987;Mosse, 1988; Bécard and Piché, 1989b; GianinazziPearson et al, 1989; Bécard and Piché, 1990; Paula and Siquiera, 1990). In particular, the hypothesis that plant phenolics could play a role as signal molecules in plant-AM fungus interactions, as in plant-Rhizobium interactions (Firmin et al, 1986;Kosslak et al, 1987;Rolfe, 1988;Djordjevic and Weinman, 1991;Hartwig and Phillips, 1991;Hungria et al, 1991), has been investigated. The isoflavonoids formononetin and biochanin A, identified in clover roots, have been shown to increase AM infection in white clover Siqueira et al, 1991) and the flavonoids hesperitin, naringenin and apigenin have been reported to stimulate Gigaspora margarita hyphal growth in vitro (Gianinazzi-Pearson et al, 1989), as has the widely occurring flavone quercetin in the presence of CO 2 (Bécard et al, 1992) Knowing that AM infection can increase the accumulation of phytoalexins and associated isoflavonoids in soybean roots (Morandi et al, 1984;Morandi and Gianinazzi-Pearson, 1986;Morandi, 1989) and that these compounds are generally exuded into the rhizosphere (D'Arcy-Lameta, 1984), we tested the effect of 2 soybean isoflavonoids (glyceollin I and coumestrol) and quercetin on in vitro spore germination, hyphal growth and vesicle formation of Gigaspora margarita.…”
Section: Introductionmentioning
confidence: 99%